A two-dimensional, two-level framework for achieving corporate sustainable development : assessing the return on sustainability initiatives - Wu, L.; Subramanian, N.; Gunasekaran, A.; Pawar, K.; Doran, D. (Wiley, 2018)
Sustainability studies in operations management have reported the positive effects of lean, green, and social management systems on various dimensions of a firm’s sustainability performance. However, despite its high importance and relevance, the time dimension of sustainability has not been systematically considered. This paper re-categorizes the well-identified sustainability initiatives based on a time dimension and empirically validates the categorization. Structural equation modeling (SEM) analyses were performed using data collected from 284 Chinese automotive firms. The results suggest that various lean and reactive green practices can be categorized as “short-term sustainability initiatives” because the effects of implementing these practices can be seen in a short period of time. Specifically, the benefits of implementing short-term sustainability initiatives can be further strengthened and reinforced in the long run by implementing corporate social responsibility CSR) practices. In addition, our findings also demonstrate that to fully realize the potential associated with CSR practices, firms need to be long-term oriented and adopt a wait and watch approach.